Enantioselective ortho‐CH Cross‐Coupling of Diarylmethylamines with Organoborons. (14th September 2015) - Laforteza, Brian N.; Chan, Kelvin S. L.; Yu, Jin‐Quan
Abstract The commonly used para‐nitrobenzenesulfonyl (nosyl) protecting group is employed to direct the CH activation of amines for the first time. An enantioselective ortho‐CH cross‐coupling between nosyl‐protected diarylmethylamines and arylboronic acid pinacol esters has been achieved utilizing chiral mono‐N‐protected amino acid (MPAA) ligands as a promoter.